Occurrence of Clavibacter michiganensis subsp. michiganensis, the causal agent of bacterial canker of tomato, in Syria - FTAYEH, Radwan; von TIEDEMANN, Andreas; KOOPMANN, Birger; ABU-GHORRAH, Mahmoud; RUDOLPH, Klaus (Phytopathologia Mediterranea, 2010)
Several surveys were carried out to evaluate the occurrence of bacterial canker of tomato caused by Clavibacter michiganensis subsp. michiganensis (Cmm) in Syria, especially in the North-West provinces Latakia and Tartous. The surveys revealed typical disease symptoms in greenhouses where the tomato cvs. Dima, Huda and Astona were grown, such as dark brown to black lesions on the leaf margins, wilting of whole plants, stunting, and vascular discoloration. The disease incidence in such greenhouses was 15% in the spring of 2007, and up to 70% by the end of July. Ten isolates obtained from diseased plants at different locations in these two provinces were identified as Clavibacter michiganensis subsp. michiganensis using classical microbiological tests as well as PCR. This is the first detailed proof of the occurrence of bacterial canker of tomato in Syria.